Comparison of the Central and Peripheral Corneal Stromal Demarcation Line Depth in Conventional Versus Accelerated Collagen Cross-Linking. Issue 11 (November 2015) - Ng, Alex L. K.; Chan, Tommy C. Y.; Lai, Jimmy S. M.; Cheng, Arthur C. K.
Abstract : Purpose: To compare the stromal demarcation line depth at the corneal center and its periphery in conventional versus accelerated collagen cross-linking (CXL). Methods: Patients with keratoconus who received either conventional 30-minute CXL with 3.0 mW/cm 2 irradiation intensity (group 1) or accelerated 10-minute CXL with 9.0 mW/cm 2 irradiation intensity (group 2) were included. The stromal demarcation line at the corneal center and 3-mm periphery measured at the first postoperative month using anterior segment optical coherence tomography were compared. Results: Thirty-three patients were included (18 in group 1, 15 in group 2) in this study. The mean demarcation line depth at center was 295 ± 62 μm in group 1 and 203 ± 45 μm in group 2 ( P < 0.001). The mean depths at 3-mm periphery (nasal, temporal, superior, and inferior) in group 1 were 260 ± 64 μm, 269 ± 44 μm, 232 ± 46 μm, and 242 ± 66 μm, respectively. The corresponding measurements in group 2 were 204 ± 62 μm, 201 ± 55 μm, 196 ± 68 μm, and 189 ± 53 μm. Apart from the superior peripheral cornea ( P = 0.064), the demarcation line depth measured at other peripheral regions was deeper in group 1 compared to that of group 2 ( P < 0.015). The peripheral demarcation line depth was significantly shallower than observed in the central line depth for group 1 ( P = 0.001), but not for group 2 ( P = 0.177). Conclusions: The stromal demarcation line depth was shallower after accelerated CXL compared to that of conventional CXL at the corneal center and its periphery. The volume of cross-linked stroma appears to be larger after conventional CXL compared to its accelerated counterparts.